Simulated Root Resorption: A New Study Model - Ghoddusi, Jamileh; Asgary, Saeed; Parirokh, Masoud; Eghbal, Mohammad Jafar; Vatanpour, Mahdi; Shahrami, Fatemeh (Iranian Endodontic Journal, 2008)
INTRODUCTION: The aim of this innovative study was to regenerate a condition that makes it possible to carry out researches in the field on a variety of resorption. MATERIALS AND METHODS: In order to develop apical resorption, the root canals of selected teeth were instrumented and then drilled with #4 Gates Glidden drills. In the next stage, the teeth were submerged in melted rose wax up to 3 mm to the apex. The waxed teeth were submerged in 20% sulfuric acid for 4 days. After that, all samples were evaluated under stereomicroscope and also the SEM. RESULTS: Images showed areas with different pattern of resorption in root apex and entire root canals in all samples. CONCLUSION: Simulation of the root resorption can be helpful in many experimental studies.